Experience with Antibiotics in the Treatment of Ulceronecrotic Tonsillitis Due to Vaccination by Tabletted Pox Vaccine - V. P. Bondarev; I. V. Borisevich; S. A. Melnikov; A. V. Kaskov; E. E. Shagarov; N. K. Chernikova; T. V. Dorokhina; A. V. Rylov; T. A. Bondareva; A. I. Terentyev (Антибиотики и Химиотерапия, 2020)
Clinical trials of tabletted pox vaccine revealed development of tonsillitis as a postvaccinal reaction in some volunteers: ulceronecrotic lesions in the tonsils, lymphadenitis, hyperthermia and asthenia. The main cause of the local inflammatory reactions was activation of the host opportunistic microflora including hemolytic streptococci and Staphylococcus aureus. For the treatment of the infectious complications systemic antimicrobials, such as benzylpenicillin, amoxicillin, ampicillin, cefazolin and fluoroquinolones (ciprofloxacin) in combination with the symptomatic therapy were used. The treatment course of 9 days provided complete elimination of the postvaccinal reactions, the specific antibody generation being not affected.